Ventricular Rupture due to Myocardial Infarction without Obstructive Coronary Artery Disease - Hendrik Lapp; Marcel Keßler; Thomas Rock; Franz X. Schmid; Dong-In Shin; Alexander Bufe; Heinrich G. Klues; Christian Blockhaus (Case Reports in Cardiology)
An 87-year-old woman presenting with myocardial infarction and ST-segment elevation in the electrocardiogram suffered from pericardial effusion due to left ventricular rupture. After ruling out obstructive coronary artery disease and aortic dissection, she underwent cardiac surgery showing typical infarct-macerated myocardial tissue in situ. This case shows that even etiologically unclear and small-sized myocardial infarctions can cause life-threatening mechanical complications.